2022
DOI: 10.1073/pnas.2204706119
|View full text |Cite
|
Sign up to set email alerts
|

Oropouche orthobunyavirus infection is mediated by the cellular host factor Lrp1

Abstract: Oropouche orthobunyavirus (OROV; Peribunyaviridae ) is a mosquito-transmitted virus that causes widespread human febrile illness in South America, with occasional progression to neurologic effects. Host factors mediating the cellular entry of OROV are undefined. Here, we show that OROV uses the host protein low-density lipoprotein–related protein 1 (Lrp1) for efficient cellular infection. Cells from evolutionarily distinct species lacking Lrp1 were less permissive to OROV infection than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
(51 reference statements)
3
16
1
Order By: Relevance
“…Moreover, using RVFV as a model, we observe that cholesterol as well as endosomal acidification are involved in the positive influence of LRP1 on infection. In agreement with these findings, recent studies (published while our manuscript was in preparation) showed that LRP1 acts as a receptor for RVFV and the Oropouche orthobunyavirus (OROV) by binding to the viral envelope proteins and mediating their entry into the cytoplasm [33,34]. Strikingly, LRP1 is a transporter that can overcome the blood-brain barrier [35].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Moreover, using RVFV as a model, we observe that cholesterol as well as endosomal acidification are involved in the positive influence of LRP1 on infection. In agreement with these findings, recent studies (published while our manuscript was in preparation) showed that LRP1 acts as a receptor for RVFV and the Oropouche orthobunyavirus (OROV) by binding to the viral envelope proteins and mediating their entry into the cytoplasm [33,34]. Strikingly, LRP1 is a transporter that can overcome the blood-brain barrier [35].…”
Section: Discussionsupporting
confidence: 76%
“…The results by us and others [33, 34] indicate that LRP1 is facilitating attachment and entry for a series of viruses. On the other hand we found that EMCV is not dependent on LRP1, and Schwarz et al reported the same for the Zika flavivirus (ZIKV) [34]. Thus, LRP1 appears to be a broad, but not entirely general host factor for viruses.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Low-density lipoprotein (LDL) receptors belong to an evolutionarily ancient family of endocytic receptors that are known to be hijacked as docking sites by a group of viruses ( 51 , 52 ), bacterial toxins ( 53 , 54 ), and endogenous proteins that are associated with Alzheimer's disease ( 55 , 56 ). Recently, Rift Valley fever virus ( 57 ) and Oropouche orthobunyavirus ( 58 ) were shown to bind LRP1, and the low-density lipoprotein receptor class A domain-containing 3 (LDLRAD3) was discovered to act as a receptor for Venezuelan equine encephalitis virus ( 59 ). Furthermore, LRP1 was also found to be an important host factor for the different stages of RNA virus infection, including VSV, Sandfly fever Sicilian virus, encephalomyocarditis virus, as well as Middle East respiratory syndrome coronavirus (MERS-CoV), severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1), and SARS-CoV-2 ( 60 ).…”
Section: Discussionmentioning
confidence: 99%